2017
DOI: 10.1186/s40557-017-0176-x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic sclerosis due to crystalline silica exposure among jewelry workers in Korea: two case reports

Abstract: BackgroundOccupational exposure to crystalline silica is a potential risk factor for various systemic autoimmune diseases including systemic sclerosis. The etiology of systemic sclerosis is not conclusively known, but there are epidemiological studies that show the relationship between exposure to crystalline silica and risk of systemic sclerosis. Here we report, for the first time, two cases of crystalline silica-related systemic sclerosis in patients who worked in crystal processing in the jewelry-manufactur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…There is convincing evidence that autoimmune connective tissue diseases including systemic sclerosis (SSc), rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), anti-neutrophil cytoplasmic antibody (ANCA) positive vasculitis, and overlap syndromes have been associated with silicosis. [ 6 10 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is convincing evidence that autoimmune connective tissue diseases including systemic sclerosis (SSc), rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), anti-neutrophil cytoplasmic antibody (ANCA) positive vasculitis, and overlap syndromes have been associated with silicosis. [ 6 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of idiopathic SSc in women is reported to be up to 14 times higher than that in men. [ 10 ] Silica may have a fundamental pathogenic role in the otherwise scarce cases of male SSc as the majority of patients with SSc exposed to silica are males (96% according to systemic review and meta-analysis) due to its occupational relevancy. [ 6 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Occupational exposure to crystalline silica is associated with silicosis, lung cancer, pulmonary tuberculosis, and chronic obstructive pulmonary disease [ 11 ]. Moreover, silicosis patients often develop autoimmune diseases [ 12 , 13 , 14 ]. It has been reported that experimental chronic intratracheal exposure to crystalline silica causes granuloma formation and/or fibrosis in rats [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact this name was abandoned after it was realized Bramwell discovered this association long before Erasmus . This syndrome is described in some specific industrial workers, like stonemasons, gold miners, marble workers, jewelry workers, denim sandblasting workers, ceramic workers and dental technicians . According to a large meta‐analysis of 15 case‐control studies, the odds ratio of developing SSc for the patients who were exposed to silica is denoted as 2.81 (95% CI 1.86‐4.23; P < 0.001) .…”
mentioning
confidence: 99%
“…In the treatment decision of Erasmus syndrome, severity, duration and progression rate of ILD is important, because it is the main cause of morbidity and mortality. In reported cases with Erasmus syndrome (methyl)prednisolone, methotrexate, endothelin receptor antagonists, acetyl salicylic acid, amlodipin/nifedipin are the medicines that have most commonly been used . In one study it was shown that SSc‐related ILD mostly progresses in the first 4 years of the disease .…”
mentioning
confidence: 99%